Creating a visual music interface via emotion detection - Lim, Clement Shi Hong. (2010)
In this technological age, the number of digital music files inside personal computers is expanding at an exponential rate. Furthermore, with the growing market of portable digital audio players, music is now easily accessible to the general public. However, there is one group of people that is the deaf who are unable to find a satisfying audio player that allows them to appreciate music in a meaningful way.